ŚŪNYATĀ AND KOKORO: SCIENCE–RELIGION DIALOGUE IN THE JAPANESE CONTEXT. Issue 1 (March 2015) - Kim, Seung Chul
Abstract When we read books or essays about the dialogue between "religion and science, " or when we attend conferences on the theme of "religion and science, " we cannot avoid the impression that they actually are dealing, almost without exception, not with a dialogue between "religion and science, " but with a dialogue between "Christianity and science." This could easily be affirmed by looking at the major publications in this field. But how can the science–religion dialogue take place in a world where conventional Christian concepts of God, religion, and science are foreign and unfamiliar? Is the critique that the scientist plays God still valid when there is no "God" at all? This article tries to answer the questions mentioned above, and seeks to sketch out some aspects of the science–religion dialogue in Japan which I believe could contribute a new paradigm for understanding and describing ultimate reality.